The Ben Gurion University of the Negev (BGU) - Regional Alcohol and Drug Abuse Research (RADAR) Center conducts research, education and training about substance use.with the collaboration of CUT University Department of Nursing Mental health Sector - Sokratous, Sokratis (My University, 2026)
The Ben Gurion University of the Negev (BGU) - Regional Alcohol and Drug Abuse Research (RADAR) Center conducts research, education and training about substance use. The United States National Institute on Drug Abuse (NIDA) has given recognition and award to the RADAR Center for its contributions to scientific diplomacy through outstanding efforts in international collaborative research.